2016
DOI: 10.20471/acc.2016.55.02.19
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Low Molecular Weight Heparin in Women With Hereditary Thrombophilia for Good Perinatal Outcome

Abstract: SUMMARY -Th e aim of the study was to establish the importance of low molecular weight heparin (LMWH) treatment for good pregnancy outcome in patients with hereditary thrombophilia. Th is retrospective study included 70 patients with inherited thrombophilia who gave birth at Zagreb University Hospital Center in the period from January 2014 to January 2015. Fifty-seven women were treated and 13 women were not treated with LMWH. Perinatal outcome was signifi cantly better in women with hereditary thrombophilia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…To exclude other causes of thrombophilia (besides pregnancy as a hypercoagulable state) in spite of negative history data, our patient was referred to hematologist. In case of future pregnancies, prophylactic dosage of LMWH should be considered ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…To exclude other causes of thrombophilia (besides pregnancy as a hypercoagulable state) in spite of negative history data, our patient was referred to hematologist. In case of future pregnancies, prophylactic dosage of LMWH should be considered ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a review of the full texts of 133 studies, 111 studies were excluded, mainly because they were reviews, had no controls, or included individuals without inherited thrombophilia. Finally, 22 studies, including 12 cohort studies and 10 randomized controlled trials, were identified as eligible and included in the present systematic review and meta-analysis 13,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). No eligible gray literature was found.…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%
“…Azoknál a terhes nőknél, akiknek visszatérő vetélés volt a kórelőzményében, és alacsony molekulasúlyú heparint (LMWH) kaptak, jobbak voltak a perinatalis következ-mények. Az LMWH alkalmazása indokolt az örökletes thrombophiliában szenvedő nők esetében [26,27,28].…”
Section: Orvostudományi éRtesítőunclassified